Comparative analysis of plyometric training protocols in volleyball: a meta-analysis - Ali, S.; Barrutia Barreto, I.; Gürkan, A. C. (International Journal of Disabilities Sports and Health Sciences, 2024)
Purpose: This meta-analysis synthesizes findings from 40 research studies to comprehensively examine the impact of plyometric training protocols on overall performance outcomes in volleyball athletes. Method: A systematic search identified relevant studies on plyometrics and volleyball performance. Data on training programs, performance measures, and outcomes were extracted. Statistical analysis assessed the overall effect size and addressed potential variation between studies. Findings: The constant-effects version revealed a giant wonderful common impact (Fisher r-to-z converted correlation coefficient = 0.7531, 95% CI: 0.6952 to 0.8110), affirming the fine relationship between plyometrics and volleyball overall performance. However, the random-effects model indicated giant heterogeneity among authentic effects (I² = 78.53%), prompting a radical exploration of ability sources of variability. Despite diagnosed limitations, inclusive of heterogeneity and ability publication bias, this meta-analysis underscores the want for standardized protocols and in addition studies to refine training strategies. Conclusion: The importance of this analysis lies in its contribution to proof-primarily based practices, providing valuable insights to coaches and practitioners in search of to optimize plyometric training for volleyball athletes. As a complete reference, it courses destiny research endeavors and advances know-how within the nuanced courting between plyometrics and volleyball.